Livestock component as a source in reduction of nutritional poverty– An evidence from rural Tamil Nadu - KUMAR, G SENTHIL; SELVAKUMAR, K N; PRABU, M; PANDIAN, A SERMA SARAVANA; VALLI, C; KANNADHASAN, M S (The Indian Journal of Animal Sciences, 2022)
The average per capita intake of cereals, pulses, milk and egg and meat (including fish) were estimated to be 300 g/ day, 80 g/day, 179.73 g/day, 23.484 numbers per annum and 0.708 kg / month, respectively which were found to be lower than Indian Council of Medical Research recommendations. The daily per capita intake of calorie, protein and fat were estimated to be 1,846 kcal, 43.34 g and 20.21 g which were lesser than the recommendations of the Planning commission. The prevalence of nutritional poverty was noticed to be higher than the economic poverty irrespective of occupational category. Further, the incidence of nutritional poverty was the highest among agricultural labourers (100%), followed by fishermen (94.12%) and non-farm workers (92.26%). However, it was comparatively lesser among crop cultivator (72.63%), livestock farmer (73.40%) and crop + livestock farmers (75.53%). Crop cultivators, livestock farmers and crop + livestock farmers were found to receive considerable macro-nutrients and thus there was lesser incidence of nutritional poverty when compared to other occupational groups.